Spontaneous Bilateral Tubal Gestation: A Rare Case Report - Marwah Sheeba; Gupta Supriya (Case Reports in Obstetrics and Gynecology)
Here a case is presented where the woman after a positive pregnancy test underwent medical abortion for unwanted pregnancy without ultrasound confirmation of intrauterine pregnancy. On persistence of symptoms, a second opinion was procured, when examination and a transvaginal ultrasound scan revealed ruptured unilateral tubal ectopic pregnancy. However upon subsequent laparotomy (considering deteriorating hemodynamic status of the patient), intraoperatively it turned out to be a bilateral tubal ectopic gestation.